2020
DOI: 10.1002/apj.2559
|View full text |Cite
|
Sign up to set email alerts
|

Low‐voltage and ion‐free‐reverse‐migration electrically regenerated mixed‐bed ion exchange for MEG desalination

Abstract: An improved electrical regeneration method of ion exchange was proposed to enhance the feasibility of applying ion exchange for mono-ethylene glycol (MEG) desalination and simplify the existing MEG regeneration process in deepwater gas fields. Compared with the latest electrical regeneration process named membrane-free electrodeionization (MFEDI), this method required lower voltage, did not consume high purity water, and eliminated ion backward migration in principle. These improvements were achieved by changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This patent presented a system to remove divalent cations from rich MEG using a cation exchange resin that adsorbs the divalent cations in the rich MEG prior to its entry into a flash separator [41,42]. In 2020, He S. et al, published their work on an electrically regenerated mixed bed ion exchange resin for MEG desalination [43]. Ion exchange for MEG desalination is claimed to be less energy intensive compared to the volatility-based desalination by heating under vacuum.…”
Section: Meg Desalinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This patent presented a system to remove divalent cations from rich MEG using a cation exchange resin that adsorbs the divalent cations in the rich MEG prior to its entry into a flash separator [41,42]. In 2020, He S. et al, published their work on an electrically regenerated mixed bed ion exchange resin for MEG desalination [43]. Ion exchange for MEG desalination is claimed to be less energy intensive compared to the volatility-based desalination by heating under vacuum.…”
Section: Meg Desalinationmentioning
confidence: 99%
“…The result indicated that the electrically regenerated mixed-bed ion exchange could be a promising prospect for MEG desalination in deep-water gas field operations. In recent times, research has shown a successful application of an ion exchange technology for MEG desalination [43]. The technical challenge as of today is the development of efficient regeneration of the ion exchange resin used for the MEG desalination.…”
Section: Meg Desalinationmentioning
confidence: 99%